2020
DOI: 10.18203/2320-1770.ijrcog20203296
|View full text |Cite
|
Sign up to set email alerts
|

Cholestasis of pregnancy: effects on maternal and fetal outcome

Abstract: Background: Intrahepatic cholestasis of pregnancy (ICP) typically occurs in late pregnancy affecting 1.5-2% pregnancies. Limited data is available regarding its fetal and maternal implications. This study aims to assess the impact of ICP on maternal and fetal outcome.Methods: A total 200 patients with pruritus in later half of pregnancy were studied over a period of 18 months out of which 135 were diagnosed as ICP. Clinical and biochemical parameters like serum aspartate aminotransferase, alanine aminotransfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Our findings were similar to study conducted by Hassan N et al (2020). 9 This was in contrast to the study conducted by Sharma et al (2018) 10 where no significant difference was observed between liver function test parameters and serum bile acid with the mode of delivery.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Our findings were similar to study conducted by Hassan N et al (2020). 9 This was in contrast to the study conducted by Sharma et al (2018) 10 where no significant difference was observed between liver function test parameters and serum bile acid with the mode of delivery.…”
Section: Discussioncontrasting
confidence: 60%
“…Garcia-Flores et al (2015) 13 conducted a prospective observational study in 145 pregnant patients with persistent pruritus and concluded that IHCP patients had higher rate of NICU admission and overall neonatal morbidity. According to Hassan et al (2020) 9 a high occurrence of NICU admissions (49.6% versus 15.4%) was observed in abnormal serum bile acid than the controls (p < 0.05).…”
Section: Discussionmentioning
confidence: 92%
“…In both women with ICP and those without, IOL may be associated with various complications. However, in women with ICP, timely intervention at 37-38 gestational weeks will reduce adverse outcomes for the mother and the baby [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Though, maternal consequences of ICP are benign; however, clear association is seen amongst ICP and higher prevalence of fetal distress, pretmature delivery, and sudden intrauterine demise. Most common symptom was pruritus and most of the patients developed pruritus between 32weeks to 36 weeks period of gestation [12] . In this study, most of the women had delivery at term which contrasted with the study by Senocak et al, [13] most of the women delivered at ≤37 weeks' gestation.…”
Section: Discussionmentioning
confidence: 99%